2017
DOI: 10.1002/2016jd025852
|View full text |Cite
|
Sign up to set email alerts
|

Monthly top‐down NOx emissions for China (2005–2012): A hybrid inversion method and trend analysis

Abstract: We develop an approach combining mass balance and four‐dimensional variational (4D‐Var) methods to facilitate inversion of decadal‐scale total nitrogen oxides (NOx = NO + NO2) emissions. In 7 year pseudo‐observation tests, hybrid posterior emissions have smaller normalized mean square error (NMSE) than that of mass balance when compared to true emissions in most cases and perform slightly better in detecting NOx emission magnitudes and trends. Using this hybrid method, OMI NO2 satellite observations and the GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 123 publications
(223 reference statements)
1
72
0
1
Order By: Relevance
“…These describe trends in aerosol presence for the regions over the entire time range covered by the time series. port models (Qu et al, 2017). Streets et al (2013) reviewed the current capability to estimate emissions from space, and in this section we highlight studies of emissions using OMI data that have been published subsequently.…”
Section: Top-down Emissions Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…These describe trends in aerosol presence for the regions over the entire time range covered by the time series. port models (Qu et al, 2017). Streets et al (2013) reviewed the current capability to estimate emissions from space, and in this section we highlight studies of emissions using OMI data that have been published subsequently.…”
Section: Top-down Emissions Estimatesmentioning
confidence: 99%
“…For total column O 3 the average differences were < 12 DU (or 3.9 %) with OMI greater than Pandora. Reed et al (2015) also compared Pandora with OMI during the Baltimore/Washington campaign and found that OMI pixel size, clouds, and aerosols affected OMI retrievals causing differences between Pandora and OMI of up to 65 % for total column NO 2 and 23 % for total column O 3 .…”
Section: Discover-aqmentioning
confidence: 99%
“…The model adjoint is first described by Henze et al (2007) for aerosols and Kopacz et al (2009) for carbon monoxide. It has been highly validated and applied in studies to analyze aerosol sensitivities and constrain aerosol sources in the United States Zhu et al, 2013;Mao et al, 2015) and China (Kharol et al, 2013;Zhang et al, 2015Zhang et al, , 2016Qu et al, 2017).…”
Section: The Geos-chem Adjointmentioning
confidence: 99%
“…Here we 10 calculate the AMF by applying the local OMI scattering weights from the operational retrieval to the GEOS-Chem HCHO vertical profile (Qu et al, 2017 Single-scene measurement error includes (1) the spectral fitting error reported as part of the operational product, and (2) the error in the AMF calculation, which increases from 15% under clear sky conditions to 20% at a cloud fraction of 0.3 (Millet et al, 2006). We increase the spectral fitting error by a factor of 1.59, the same factor used to correct the mean bias in OMI VCDs.…”
Section: Omi Observationsmentioning
confidence: 99%